1997
DOI: 10.1021/jf970246w
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Quinone Reductase by Withanolides Isolated from Physalis philadelphica (Tomatillos)

Abstract: The fruits of Physalis philadelphica, known commonly as tomatillos, are an ingredient of the condiment “salsa verde”. As part of an ongoing project to discover natural product cancer chemopreventive agents, an ethyl acetate-soluble extract of the commercially available fresh fruits of P. philadelphica was found to induce quinone reductase activity in cultured Hepa 1c1c7 murine hepatoma cells. Bioassay-directed fractionation of an EtOAc extract of the fruits, aided by LC/MS, led to the isolation of a series of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
0
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 22 publications
2
60
0
1
Order By: Relevance
“…It is well known that Physalis peruviana has many pharmaceutical beneficial effects. A variety of molecules from P. peruviana, were reported to be medically beneficial (Chiang et al, 1992;Dimayuga et al, 1998;Kennelly et al, 1997).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that Physalis peruviana has many pharmaceutical beneficial effects. A variety of molecules from P. peruviana, were reported to be medically beneficial (Chiang et al, 1992;Dimayuga et al, 1998;Kennelly et al, 1997).…”
Section: Resultsmentioning
confidence: 99%
“…The fruits of plant have high nutritional value because of possessing high vitamins content, minerals and antioxidants. These plants have also potential medicinal properties like anti-bacterial, antiinflammatory, and antioxidant properties (Caceres et al, 1991;Chiang et al, 1992;Dimayuga et al, 1998;Kennelly et al, 1997;Yen et al, 2010). Besides this plant is known to induce apoptosis in different phases and has anti-cancer activity (Yen et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…4.2.4.) (103)(104)(105). With the exception of withanone (513), all the withanolides were potent QR inducers with activity comparable to or better than the reference compound, sulforaphane, a known chemopreventive agent.…”
Section: Cancer Chemopreventive Activitymentioning
confidence: 98%
“…(102). The known withaphysacarpin (195) and its 3-methoxy derivative, 196, with a 16b-hydroxy group, were isolated from the fruits of Physalis philadelphica and the configuration of the lactone methyl groups was established as shown, for both compounds (103). LC-MS analysis of an ethyl acetate extract of the plant suggested that 196 may occur naturally although in minor amounts, being generated to a larger extent as a result of the extraction procedure.…”
mentioning
confidence: 97%
“…Tomatillo is known for its protein (11%) and low fat content (18%) [12]. Nutritional analysis have not examined yet the extraction and quantification of carotenoids, despite its high (58%) carbohydrate content and the quinone reductase activity found in hepatoma cells for one extract of Physalis philadelphica [13]. In this work, a low concentration of β-carotene and lutein was demonstrated in two species of tomatillo and the relative amounts varied with the cooking procedures, as reported in Table 2.…”
Section: Resultsmentioning
confidence: 99%